THE INFLUENCE OF PASSIVE TOBACCO EXPOSURE AND PHYSICAL EXERCISE ON BONE TISSUE OF YOUNG RATS - Urban, Jacqueline Bexiga [UNESP]; Trindade Camargo, Regina Celi [UNESP]; Costalonga, Regiane Rocha [UNESP]; Quirino Louzada, Mario Jefferson [UNESP]; Fernandes, Romulo Araujo [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP] (Atha Comunicacao & Editora, 2017)
Objective: The objective of this study is to investigate the effect of passive smoking during pregnancy and associated with swimming on bone area growth, bone mineral density (BMD), and bone mineral content (BMC). Methods: The offspring was grouped by control matrices (G1) and passive smokers (G2). The offspring was regrouped in eight subgroups, with exposure to smoking (2x/day) and physical exercise (1 session/day), respecting the group of matrices in: sedentary control (G1CS and G2CS), swimming control (G1CN and G2CN), sedentary passive smoker (G1FS and G2FS), and passive smoker swimmer (G1FN and G2FN). The area, BMD and BMC were measured by the tibia and femur and analyzed by densitometer. The results were analyzed by One-Way ANOVA test with Tukey post-test, with a significance level of 5%. Results: In the tibia BMC study, a better rate was observed in G2CN group when compared to G1CS, G1CN and G1FN (p <= 0.023). When assessing BMD in the femur, a higher density ratio was observed in G1FS group when compared to G2CS, G2CN, G2FS and G2FN (p<0.008). In the tibia study, the animals of the G1FS group had higher rates when compared to G2CS and G2FN groups (p <= 0.007). Conclusions: The model of male offspring exposed to passive smoking during fetal development showed a strong decrease in the analyzed parameters.
Keywords: Exercise; Tobacco smoke pollution; Rats, Wistar/growth & development; Lactation; Birth weight